EFEK TEPI PADA KOMUNITAS BURUNG ANTARA TEGAKAN AGATHIS DAN PUSPA HUTAN PENDIDIKAN GUNUNG WALAT, JAWA BARAT - Fadila Tamnge; Yeni A. Mulyani; Ani Mardiastuti (Media Konservasi, 2016)
Gunung Walat University Forest (GWUF) consist of several type of tree, two of them are Agathis (Agathis loranthifolia) and Schima (Schima walichii) stand. Different types of plantation forest might create fragments that affect bird communities. As a consequence of habitat fragmentation, the amount of habitat ecotone is increase and create edge effect. The objectives of this study were to (1) analyze whether there were edge effects for birds on Agathis and Schima stand, (2) analyze bird species found in ecotonal and species in non-ecotonal habitats, (3) analyze how birds responded to the presence of ecotone. This research was conducted in Agathis and Schima stands (edge and interior) in GWUF. Birds were surveyed by using point count. Bird diversity was calculated using Shannon-Wienner Indices, followed by Kruskal-Wallis tests, and similarity of communities was tested by using Bray-Curtis. Bird response to ecotone were described using histograms. The results showed that the abundance (Kruskal-Wallis test; χ2 =11,42, df=2, P<0,05) and species richness (Kruskal-Wallis test; χ2 =10,39, df=2, P<0,05) were higher in ecotone. Each stand has specialist species. Ecotonal habitat consists of Cacomantis sonneratii, Cacomantis sepulcralis, Surniculus lugubris, Centropus bengalensis, Hirundo tahitica, and Pycnonotus aurigaster. Schima stand consists of Enicurus leschenaulti, Oriolus chinensis, and Stachyris melanothorax, while Agathis stand do not have specialist species. About 41% of the bird species were able to be mapped into model as ecotone neutral-generalist, ecotone shy-specialist, ecotone conspicuous- specialist, and ecotonal species.Keywords: bird communities, ecotone, edge effect, GWUF